COVID-19 infection in pregnant women with preeclampsia and HELLP syndrome, with possible vertical transmission to the fetus: a case report - Retnowati, Sulistiari; Wahyuni, Alfaina; Pramono, Nabila A (Universitas Muhammadiyah Purwokerto, 2022)
Background: During pregnancy, a woman's immune cells undergo cellular and functional alterations, rendering them more vulnerable to illness. Preeclampsia and HELLP syndromes are pregnancy problems and one of Indonesia's leading causes of maternal mortality; COVID-19 infection would exacerbate the situation. The evidence for COVID-19 vertical transmission is not well established, and the report on the incidence of vertical transmission, especially in Indonesia, is still limited.Case presentation: We discuss the case of a 26-year-old, 36 weeks of gestation, with preeclampsia and HELLP syndrome, who was infected with COVID-19 and got severe pneumonia and ARDS. The infant was born by cesarean section, and there was no contact between the infant and mother following delivery. Based on the results of the PCR examination, the baby was also confirmed to have COVID-19 without any symptoms.Conclusion: Vertical transmission during pregnancy is possible in women with a severe type of COVID-19 with preeclampsia and HELLP syndrome.